Evolutions in sustainable investing strategies, funds and thought leadership - Krosinsky, Cary (Wiley finance series, 2012)
Real-world guidance for investment professionals on delivering attractive risk-adjusted and opportunity-directed returns across asset classes and regionsFilled with interviews with leading practitioners, this book weaves a narrated web around best sustainable investment practices, guiding readers specifically on investing their assets and with specific sustainability trends in mind, such as increasing constraints on global resources. Offers a clear road map to success by some of the most respected names in the field Includes interviews with leading practitioners Clearly explains how to get sustainable investing done Sustainable Investment is a practitioner's book specifically laying out how this investment philosophy is being practiced. It explicitly considers future social and environmental trends in financial decision making, to provide the best risk-adjusted and opportunity-directed returns for investors--Provided by publisher.